Evaluation of the OpSens OptoWire III and Novel TAVR Algorithm to Measure Pressure Gradient During TAVR - Généreux, Philippe; Kipperman, Robert M.; Placido Disla, Jenny S.; Aldaia, Lillian; Koulogiannis, Konstantinos P.; Marcoff, Leo; Mediratta, Anuj; Slater, James P.; Zaku, Bledi; Redfors, Björn; Abdelfattah, Omar M.; Gillam, Linda D. (Journal of the Society for Cardiovascular Angiography & Interventions, 2022)
We aim to establish the degree of agreement related to gradient measurement during transcatheter aortic valve replacement (TAVR) between the OpSens OptoWire III and its new proprietary TAVR algorithm and hemodynamic value derived by catheterization and echocardiogram (transthoracic echocardiogram and transesophageal echocardiogram). The current study was a prospective, single-arm, single-center study. All subjects underwent hemodynamic assessment before and after TAVR using standard hemodynamic assessment using 2 pigtails, transthoracic echocardiogram, transesophageal echocardiogram, and the OpSens OptoWire III. The primary end point was the final post-TAVR mean gradient correlation between OpSens OptoWire III and hemodynamic values derived by catheterization. Between July 2021 and September 2021, 20 patients were enrolled. The median age was 79 [6.5] years, and 9 (45%) patients were female. The mean gradient before TAVR derived by 2-pigtail technique and the mean gradient using the OpSens OptoWire III were similar (35 ± 14 mm Hg vs 35 ± 14 mm Hg, P = 1.00), with an absolute mean difference of 2.2 ± 3.5 mm Hg and a strong correlation (r = 0.96, P < .0001). After TAVR, the mean gradient derived by 2-pigtail technique and the mean gradient using the OpSens OptoWire III were similar (2.2 ± 3.5 vs 2.8 ± 2.7, P = .16), with an absolute mean difference of 1.2 ± 1.3 mm Hg and a strong correlation (r = 0.89, P < .0001). Hemodynamic assessment derived by the OpSens OptoWire III wire and its new TAVR algorithm demonstrated excellent correlation with measurements derived by 2 pigtails both before and after TAVR. Integration of this new technology within a dedicated TAVR wire with live hemodynamic assessment could bring meaningful value to TAVR operators. [Display omitted] •Gradient measurement during TAVR using the OpSens wire was feasible and safe.•OpSens wire shows strong correlation with 2-pigtail gradient measurement during TAVR.•Invasive and echocardiographic gradient measurements were similar before TAVR.•Discrepancies between invasive and echocardiographic gradients were seen after TAVR.